PENGARUH SUPPLY AND DEMAND SONGKET TERHADAP KONDISI SOSIAL EKONOMI RUMAH TANGGA PENGRAJIN SONGKET DI DESA MUARA PENIMBUNG ILIR PADA MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT DI KOTA PALEMBANG - Fernando Jose Retana Quesada; Yunindyawati Yunindyawati; Dadang H. Purnama (Institut Pendidikan Tapanuli Selatan, 2024)
This study aims to analyze the effect of demand and supply of songket cloth during the implementation of Covid-19 restrictions in Palembang City on the socio-economic conditions of households in Muara Penimbung Ilir Village. The main sources in this study were all songket craftsmen in Muara Penimbung Ilir Village, totaling 32 respondents. Quantitatively, data collection was carried out through questionnaires (Likert scale), interviews, and observations. Logistic Regression Analysis was used to analyze the data. Based on the results of this study, supply (X1) and demand (X2) have a significant effect on the socio-economic conditions of the Songket craftsmen's families (Y). Supply and demand affect 91.3% (R Square) of the socio-economic behavior of songket producing households in the village, while the other 8.7% can be explained by other models. The Indonesian government's Covid-19 restrictions, called PPKM and PSBB, are the main cause of the decline in demand for songket cloth. The second reason for the decline in demand for songket cloth is due to the economic crisis the country is facing during Covid-19. Songket is not a staple item, so consumers choose to stop buying products in times of uncertainty.